2014
DOI: 10.1523/jneurosci.0226-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Control of Food Intake and Energy Expenditure by Nos1 Neurons of the Paraventricular Hypothalamus

Abstract: The paraventricular nucleus of the hypothalamus (PVH) contains a heterogeneous cluster of Sim1-expressing cell types that comprise a major autonomic output nucleus and play critical roles in the control of food intake and energy homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 33 publications
5
131
1
Order By: Relevance
“…Future studies should determine whether chronic intranasal administration of OT recapitulates the effects of chronic subcutaneous administration to stimulate energy expenditure in DIO nonhuman primates [26] and whether these effects translate to obese humans. Sutton and colleagues demonstrated that acute CNO-induced activation of PVN OT neurons in oxytocin-Ires-Cre mice increased Fos in thoracic sympathetic preganglionic neurons in the spinal cord [89]. OT also activated thoracic sympathetic preganglionic neurons in the cat [136] as well as the stellate ganglia in the dog [137].…”
Section: Effects Of Ot On Energy Expenditurementioning
confidence: 99%
See 2 more Smart Citations
“…Future studies should determine whether chronic intranasal administration of OT recapitulates the effects of chronic subcutaneous administration to stimulate energy expenditure in DIO nonhuman primates [26] and whether these effects translate to obese humans. Sutton and colleagues demonstrated that acute CNO-induced activation of PVN OT neurons in oxytocin-Ires-Cre mice increased Fos in thoracic sympathetic preganglionic neurons in the spinal cord [89]. OT also activated thoracic sympathetic preganglionic neurons in the cat [136] as well as the stellate ganglia in the dog [137].…”
Section: Effects Of Ot On Energy Expenditurementioning
confidence: 99%
“…Existing data indicate that OT plays a critical role in the control of energy homeostasis [26][27][28][30][31][32][34][35][36]56,62,[79][80][81][82][83][84][85][86][87][88][89]. For example, global deficiencies in either OT [90] or OTRs [91] are associated with adult-onset obesity in mice.…”
Section: Role Of Ot Signaling In Energy Balancementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, gabazine had opposite effects on body temperature in the PVN and DMH, as expected from experiments in rats (32,33), which also confirms the site selectivity of the injections. Collectively these data suggest that neither AgRP nor GABA in PVN are involved in the suppression of SSNA or HR following ArcN AgRP/NPY neuronal activation, likely because of rons in the spinal cord (25). Therefore, given the profound sympathoinhibitory effects of NPY in the PVN in both mice ( Figure 3) and rats (4, 7, 26), we next considered potential explanations for the failure of PVN BIBO3304 administered after i.p.…”
Section: Selective Activation or Inhibition Of Arcn Npy/agrp Neurons mentioning
confidence: 99%
“…Recent studies indicate that in addition to suppressing food intake, oxytocin may also reduce body weight in rodents and nonhuman primates by increasing energy expenditure (10,63,90,99,(102)(103)(104). Conversely, animals with either partial or complete loss in oxytocin signaling show decreased energy expenditure (18,45,93,99,104) and brown adipose tissue thermogenesis (18,45,93).…”
mentioning
confidence: 99%